Peningkatan Hasil Belajar IPAS Menggunakan Model Attention, Relevance, Convidence, Satisfaction di Kelas IV SDN 06 Lasi Mudo Kabupaten Agam - Haqki, Tiwi Faira; Astimar, Nelly (Asian Journal of Early Childhood and Elementary Education, 2024)
The purpose of this study was to describe the use of the Attention, Relevance, Confidence, Satisfaction model to improve student learning outcomes in IPAS learning. This research is a classroom action research (PTK) that uses qualitative and quantitative approaches. It was carried out in two cycles, where cycle I consisted of 2 meetings and cycle II consisted of 1 meeting. Classroom action research includes four stages, namely planning, implementation, observation, and reflection. The subjects of this research were teachers and 25 students of Class IV SDN 06 Lasi Mudo Agam Regency. The research data were obtained from the teaching module assessment, implementation process, and learning outcomes. Data collection techniques using test, and non-test techniques. The results showed an increase in: a) cycle I teaching modules with an average of 89.6% (Good) and cycle II 95.8% (Very Good), b) Teacher activity in the implementation of cycle I with an average of 81.25% (Fair) and cycle II 95% (Very Good), while student activity in the implementation of cycle I with an average of 81, 25% (Fair), and cycle II 95% (Very Good), c) Assessment of student learning outcomes in cycle I with an average of 77.39 (Fair) and increased in cycle II to 87.07 (Good). Based on these results it can be concluded that the Attention, Relevance, Confidence, Satisfaction model can improve the learning outcomes of students on IPAS material in elementary schools.